Project-Based Learning and Traditional Online Teaching of Research Methods During COVID-19: An Investigation of Research Self-Efficacy and Student Satisfaction - Randazzo, Melissa; Priefer, Ryan; Khamis-Dakwar, Reem (Frontiers in Education, 2021)
Research methods courses are a critical component of teaching the applications of evidence based practice in the health professions. With the shift to online learning during the Covid-19 pandemic, new possibilities for teaching research methods have emerged. This case study compares two 5-week asynchronous online graduate level research methods courses in the field of Communication Sciences and Disorders. One online section of the course used traditional methods (TDL) common in face-to-face courses with recorded slide-based lectures, written discussion forums, and a final presentation. The other online section of the course used project-based learning (PBL), which consisted of weekly projects that forced students to engage with the literature and work both collaboratively and autonomously. We measured students’ research self-efficacy and course satisfaction before and after their courses. Overall, research self-efficacy was higher for the TDL class at both time points. However, the PBL class showed a higher percent increase in research self-efficacy, specifically for more difficult and unfamiliar tasks like statistical analysis. Students in both courses were equally satisfied with their course and instructor; however, students in the PBL class reported a greater workload and level of difficulty. We interpret the results as showing benefits of PBL in facilitating greater engagement with the research literature and course content; while TDL had advantages in students’ confidence with the course, likely due to familiarity with the instructional format.